Biochar: An Effective Solution for Sustainable Agriculture and Ecosystem Restoration - Yuldashbek, Davlat; Akhmetov, Nurlan (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
This article discusses various aspects related to biochar, its production, and its environmental and agricultural benefits. Biochar is a carbon-rich material produced from biomass through pyrolysis in conditions of limited oxygen. It possesses a range of beneficial properties, such as improving soil quality, increasing its fertility, enhancing crop yield, and carbon sequestration. Biochar helps retain nutrients, improves soil water retention, and reduces greenhouse gas emissions. Its application contributes to better seed germination, seedling growth, as well as increasing plant resistance to environmental stressors and diseases. The use of biochar in different doses and pyrolysis conditions can significantly enhance its effectiveness in agriculture and ecological rehabilitation. The use of biochar for the reclamation of contaminated soils reduces the availability of toxic substances, such as heavy metals and pesticides, making this material a promising tool for ecosystem restoration. Thus, biochar represents a promising solution for improving soil and ecosystem health, reducing pollution, and mitigating the impacts of climate change, providing new opportunities for sustainable agriculture and environmental protection.